Model Praktis Kepemimpinan Kristen Adaptif: Implementasi Pendekatan Spiritual dan Edukatif di Tengah Arus Hoaks dan Disinformasi Digital - Dela Dela; Yeheskiel Dongga; Jenita Ria; Erna Erna; Oktapina Ori (Berkat : Jurnal Pendidikan Agama dan Katolik, 2025)
The era of digital disruption marked by the massive spread of hoaxes and disinformation presents a serious challenge for the church in maintaining the unity and purity of teaching. The gap between the need for a relevant leadership response and the lack of practical models that can be applied is a key problem that this study seeks to answer. This study aims to (1) analyze the essential components of an adaptive model of Christian leadership in responding to these challenges, and (2) formulate a practical framework that blends spiritual and educational strategies for church leaders. Using qualitative research methods with a literature review approach, secondary data from various scientific literature are analyzed through qualitative content analysis to build a conceptual model. The results of the study conclude that an effective leadership model is built on three main foundations: the character of a leader with integrity, in-depth knowledge of the digital and theological landscape, and practical skills in communication and education. The most effective framework is one that synergizes a spiritual approach to build the resilience of the faith of the congregation from within, with an educational approach to equip the congregation with digital literacy in the face of external threats.